Development and Validation of a Non-Cognitive Character Diagnostic Assessment Instrument for Junior High Graduates - Muchamad Aulia Arifin; Sarwi Sarwi; Djuniadi Djuniadi (Universitas Negeri Semarang, 2025)
The characteristics of the independent curriculum are assessments at the beginning, process, and end of learning to understand learning needs and the development of the learning process that students have gone through. One of the objectives of non-cognitive diagnostic assessment is to obtain information about students' initial character. The existing non-cognitive character diagnostic assessment instruments, according to the author, are good but need to be developed. The Graduate Profile Dimension in In-Depth Learning is an indicator in creating statement items for this non-cognitive character diagnostic assessment. This study aims to develop a valid and reliable non-cognitive character diagnostic assessment instrument for junior high school graduates. The design chosen in this study is Research and Development (R & D) with a 4D development model. Content and construct validity were analyzed using Aiken's V and CFA, while reliability was analyzed using the Cronbach Alpha formula. The results of Confirmatory Factor Analysis (CFA) with the help of the Lisrel program. The average content validity value from the experts was 0.96. Therefore, it can be stated that the instrument is valid. The results of the analysis show that the Construct Reliability (CR) value of 0.98 has met and even exceeded the required minimum limit value, which is 0.70. This CR value shows that the indicators in the instrument have a very good level of consistency and show very high internal consistency.